2019
DOI: 10.3389/fncel.2019.00265
|View full text |Cite
|
Sign up to set email alerts
|

Transient Potassium Channels: Therapeutic Targets for Brain Disorders

Abstract: Transient potassium current channels (I A channels), which are expressed in most brain areas, have a central role in modulating feedforward and feedback inhibition along the dendroaxonic axis. Loss of the modulatory channels is tightly associated with a number of brain diseases such as Alzheimer’s disease, epilepsy, fragile X syndrome (FXS), Parkinson’s disease, chronic pain, tinnitus, and ataxia. However, the functional significance of I A channels in these diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 129 publications
(155 reference statements)
3
36
0
Order By: Relevance
“…Our observations are consistent with findings of the effects of SK3 channel agonists in intact animals [31,38,47,48]. In conditionally SK3-deficient mice, baseline levels of striatal extracellular dopamine are increased [31] while both CyPPA spontaneous firing rate and dopamine release are decreased [49].…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…Our observations are consistent with findings of the effects of SK3 channel agonists in intact animals [31,38,47,48]. In conditionally SK3-deficient mice, baseline levels of striatal extracellular dopamine are increased [31] while both CyPPA spontaneous firing rate and dopamine release are decreased [49].…”
Section: Plos Onesupporting
confidence: 91%
“…Dopamine neuron susceptibility to excitotoxic injury is potentially relevant to a number of pathological conditions, and therefore so is the development of potential neuroprotective strategies, including the use of pharmacological modulators of SK3 channel function [ 31 34 ]. We previously showed that 1-EBIO effectively protects DN in primary cultures of ventral mesencephalon against AMPA-mediated toxicity by sustaining SK3 channel conductance [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine neuron susceptibility to excitotoxic injury is potentially relevant to a number of pathological conditions, and therefore so is the development of potential neuroprotective strategies, including the use of pharmacological modulators of SK3. channel function (Noh et al, 2019). We previously showed that 1-EBIO effectively protects DN in primary cultures of ventral mesencephalon against AMPA-mediated toxicity by sustaining SK3.…”
Section: Discussionmentioning
confidence: 98%
“…It controls the threshold for action potentials and repetitive firing in visual cortical pyramidal neurons (Yuan, Burkhalter, & Nerbonne, ), and it is critically required for the suppression of excitability in granule cells during their maturation (Shibata et al, ). I A channels and Ca 2+ ‐permeable channels (such as NMDARs) play counteracting roles in regulating neuronal excitability (Noh, Pak, Choi, Yang, & Yang, ). Furthermore, enhanced excitatory input can also negatively regulate neuronal excitability via up‐regulating the I A density (Shen et al, ).…”
Section: Discussionmentioning
confidence: 99%